2021
DOI: 10.1155/2021/8027314
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma of the Pelvis: Clinical Presentation and Overall Survival

Abstract: Introduction. Osteosarcoma is the most common sarcoma of bone. Pelvic osteosarcoma presents a significant therapeutic challenge due to potential late symptom onset, metastatic dissemination at diagnosis, and inherent difficulties of wide surgical resection secondary to the complex and critical anatomy of the pelvis. The rates of survival are well reported for osteosarcoma of the appendicular skeleton, but specific details regarding presentation and survival are less known for osteosarcoma of the pelvis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…There are reports that proximal location in the appendicular skeleton and localization in the pelvis may be poor prognosis factors. [ 9 , 10 ] Brown et al[ 9 ] reported one-, five-, and 10-year OS rates for primary OS of the pelvis as 45.6%, 26.5%, and 21.4%, respectively, for the entire cohort of the SEER database. In their study, the most important factor on survival was the presence of metastasis at presentation, while advanced age and other factors affected the surgical removal of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that proximal location in the appendicular skeleton and localization in the pelvis may be poor prognosis factors. [ 9 , 10 ] Brown et al[ 9 ] reported one-, five-, and 10-year OS rates for primary OS of the pelvis as 45.6%, 26.5%, and 21.4%, respectively, for the entire cohort of the SEER database. In their study, the most important factor on survival was the presence of metastasis at presentation, while advanced age and other factors affected the surgical removal of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Bielack et al, in a review of 1702 osteosarcoma patients, reported a 5-year OS of 28.9% for patients with pelvic osteosarcoma; this is significantly worse compared to that of patients with extremity osteosarcoma (67.3%) [ 24 ]. Other studies have reported 5-year survival rates for pelvic osteosarcoma of 18–34% [ 25 , 26 , 27 ]. Consistent with these reports, osteosarcoma was shown to have a poorer prognosis among the bone sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the optimal surgery supplemented by radiotherapy and chemotherapy remains the mainstay for OS treatment [4]. However, due to its high degree of malignancy and high incidence of metastasis, the prognosis of OS is very poor [5,6]. Hence, it is imperative to develop novel therapeutics to restrain the proliferation and invasion of OS cells, which is of great signifcance for improving the treatment outcome and survival rate.…”
Section: Introductionmentioning
confidence: 99%